2011
DOI: 10.5415/apallergy.2011.1.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition for atopy and allergic rhinitis in the Singapore Chinese population

Abstract: The prevalence of allergic diseases is high globally, but especially in developed countries, with one in five to one in four individuals affected worldwide. The World Health Organization's "Allergic Rhinitis and its Impact on Asthma 2008 Update" guidelines stated explicitly that over 600 million patients from all countries, all ethnic groups and all ages suffer from allergic rhinitis (AR). There are clear evidences to support the concept that allergic diseases are influenced by genetic predisposition and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The scope of this study was beyond a genetic investigation. However, many of the gene-based AR studies revealed no significant association with AR [51]. Allergic and non-allergic rhinitis are both similar in signs and symptoms, except that non-allergic rhinitis don’t involve the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of this study was beyond a genetic investigation. However, many of the gene-based AR studies revealed no significant association with AR [51]. Allergic and non-allergic rhinitis are both similar in signs and symptoms, except that non-allergic rhinitis don’t involve the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of AR and similar allergic diseases involves complex interactions of environmental exposure to allergens and respiratory irritants (Shusterman et al, 2003;Wang, 2005;Bousquet, 2008) as well as genetic predisposition of the individual patients (Dávila et al, 2009). Many susceptibility loci for AR and atopy have been described in various Western and Eastern populations (Bauchau and Durham, 2004;Mou et al, 2010;Wang, 2011). Results from several studies have suggested that interactions of multiple genes and environmental factors cause susceptibility to AR.…”
Section: Introductionmentioning
confidence: 97%
“…24,25,28 Actually, it was reasonable that the results from epidemiologic studies were not consistent with the results from respective functional study. This is because AR is a complex atopic disorder and is affected by many factors including both genetic and environmental factors, and different genetic backgrounds including age or ethnicity may lead to different outcomes 38,39 and other undiscovered genes involved in AR development might mask the influence of the D or I allele.…”
Section: Discussionmentioning
confidence: 99%